Characterizations of a nanocomposite biochemical-sensing membrane of γ-APTES incorporated with silica nanoparticles prepared by ultrasonic liquid atomizer spray. (1st October 2021) - Liao, Su-Yu; Tsai, Kai-Hsun; Lin, Jing-Jenn; Ching, Congo Tak-Shing; Wu, You-Lin
Abstract: Large-area and uniformly distributed 3-aminopropyltriethoxysilane ( γ -APTES) incorporated with poly-dimethylsiloxane-treated hydrophobic fumed silica nanoparticles (NPs) sensing membranes with different mixed ratios were deposited by using ultrasonic liquid atomizer (ULA) spray. Nanoscale current–voltage ( I–V ) characteristics of the deposited membranes were then characterized by using conductive atomic force microscopy. It is found that the ULA-sprayed γ -APTES plus NPs ( γ -APTES + NPs) membrane has smaller leakage current and higher breakdown voltage than does the ULA-sprayed pure γ -APTES membrane. Excellent glucose sensing performances are found when using the deposited ULA-sprayed γ -APTES + NPs as sensing membrane on polysilicon wire sensor. Further sensing performance enhancement was obtained as the γ -APTES + NPs membrane was subjected to UV illumination. Our experiment's results confirmed that the ULA spray is a promising method for large area deposition of γ -APTES + NPs membrane and that it can be utilized for biomedical sensor applications.